Effects of the PPARG P12A and C161T gene variants on serum lipids in coronary heart disease patients with and without Type 2 diabetes - (:unkn) unknown (SPRINGER, 2011)
We investigated whether PPAR-gamma 2 gene polymorphisms are associated with serum lipids and the occurrence of coronary heart disease (CHD) prospectively characterised for the presence or absence of Type 2 diabetes in a Turkish population. Our study included 202 patients with CHD (102 with diabetes, 100 without diabetes) and 105 controls. PPAR gamma genotypes were determined by PCR-RFLP technique. The PPAR gamma-C161T CC homozygote genotype was associated with significantly increased CHD risk when compared with the T allele carriers (CT+TT) in CHD patients with diabetes (OR:1.951, 95%CI: 1.115-3.415, P = 0.019), whereas PPAR gamma-P12A polymorphism was not associated with CHD risk (P > 0.05). Serum HDL-C levels were significantly lower in controls with the P12A heterozygote when compared with the P12P homozygote (P = 0.002). In the CHD patients with diabetes, CT heterozygote genotype showed higher serum triglyceride than the CC homozygote genotype (CT:2.42 +/- A 1.89 vs. CC:1.61 +/- A 0.21, P = 0.015). Our findings shows the association of these two polymorphisms with serum triglyceride levels, which was increased in the order of P12P-CC < P12P-CT < P12A-CC < P12A-CT in the CHD patients with diabetes. Furthermore, we observed that the increasing effects of the CT genotype on serum triglyceride levels could be modified by PPAR gamma P12A polymorphism (P12A-CT:2.30 +/- A 1.75 vs. P12P-CC:1.79 +/- A 1.14, P = 0.028). We suggested that homozygote CC genotype of the PPAR gamma C161T polymorphism might be associated with an increased CHD risk especially in patients with diabetes. We observed that the C161T CT heterozygote genotype shows an unfavorable effect on serum lipid profile in CHD patients with diabetes and this effect was weaken with the presence of P12P homozygote genotype.
Keywords: PPARG; Polymorphism; Coronary heart disease; Diabetes; Lipids; ACTIVATED-RECEPTOR-GAMMA; BODY-MASS INDEX; ACUTE MYOCARDIAL-INFARCTION; PRO12ALA POLYMORPHISM; ARTERY-DISEASE; RISK; ASSOCIATION; SUBSTITUTION; ATHEROSCLEROSIS; IDENTIFICATION